EEG signal analysis and characterization for the aid of disabled people - Reaz, Mamun Bin Ibne; Chowdhury, Md. Sazzad Hossien; Ibrahimy, Muhammad Ibn; Mohd-Yasin, Faisal (WIT Press, 2007)
The effectiveness of assistive devices for disabled people is often limited by the human machine interface. This research proposes an intelligent wheelchair system especially for severely disabled people based on analysing electroencephalographic signals by using discrete wavelet transform and higher order statistical methods. The system to be implemented in Field Programmable Gate Array enables an accurate and efficient system of processing signals to control the wheelchair, which makes an attractive option in the hardware realization.